(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The power bondage number is an essential specification of graphs which is standard upon the well-known power domination number. The power bondage number of a nonempty undirected graph is the least count of edges whose removal from the given graph . In this article we discuss about the power bondage number of some classes of graphs.